A checklist of species of Vorticellidae (Ciliophora: Peritrichia) epibionts of crustaceans - Mayén-Estrada, Rosaura; Utz, Laura R. Pinto (Zootaxa, 2018)
The family Vorticellidae includes 21 genera, mainly with species worldwide distributed, as free-living, and attached to diverse organisms as epibionts. The goal of this paper is to provide an updated checklist of the worldwide vorticellids reported attached to the crustaceans. We revised and checked all available records of species of vorticellids including their crustacean hosts. We found 96 vorticellid species belonging to 14 genera with at least a report on the body of 81 species of crustaceans. Four genera of ciliates (Vorticella, Pseudovorticella, Carchesium and Intranstylum) had the major number of species living as epibionts. We provide also the complete list of the species of vorticellids, and conclude the need of a taxonomic revision of the family.